10.24.5 Product Subclass 5: Pyridazino[1,6-a]indoles and Related Benzo-Fused Ring Systems - Harris,P. A. (Knowledge Updates 2021/3, 2021)
The synthesis of pyridazino[1,6-a]indoles, as well as the related indolo[1,2-b]cinnolines and indolo[2,1-a]phthalazines, are reviewed in this chapter. The most utilized methods to access pyridazino[1,6-a]indoles involve annulation of 1H-indol-1-amine derivatives.
Keywords: Referencework; Science of Synthesis; pyridazino[1,6-a]indoles; indolo[1,2-b]cinnolines; indolo[2,1-a]phthalazines; annulation; cyclization